THE RELATIONSHIP OF THORACIC KYPHOSIS WITH PULMONARY FUNCTIONS IN PATIENTS WITH OSTEOPOROSIS - Gülçin Kaymak Karataş; Gül Gürsel; Nadide Torlak Koca (Archives of Rheumatology, 2002)
In this study, the relationships of thoracic kyphosis with pulmonary function tests and respiratory muscle strength were investigated in patients with osteoporosis. Twenty women, whose mean age was 68 ± 6 years, were included in the study. Localisation and number of thoracal vertebral fractures were determined and Cobb angle was measured. Forced expiratory volume in 1 second (FEV1), forced vital capacity (FVC), FEV1/FVC, forced expiratory volume between 25% and 75% of the forced vital capacity (FEF25-75), peak expiratory flow (PEF), vital capacity (VC), residual volume (RV), total lung capacity (TLC), RV/TLC, functional residual capacity (FRCN2), expiratory residual volume (ERV), inspiratory capacity (IC), carbon monoxide diffusion capacity of the lung (DLCO), maximum inspiratory pressure (MIP) and maximum expiratory pressure (MEP) were measured. Pulmonary function tests were within normal limits, and mouth pressures were low. A negative correlation between Cobb angle and FVC%, and a positive correlation between Cobb angle and FEV1/FVC were determined (Pearson r: -0.46 and r: 0.46, respectively, p<0.05). A negative correlation was determined between fracture number and FVC%, FEV1%, VC%, MIP, MIP% (Spearman r: -0.56, -0.59, -0.55, -0.58 and -0.57, respectively, p<0.05). When patients were divided into group-I (<2 vertebral fracture) and group-II (≥2 vertebral fractures), results of pulmonary function tests and respiratory muscle strength were lower in group-II. But the difference between the groups was significant only in FVC%, FEV1%, VC%, MIP and MIP% (p<0.05). In this study; the most prominent finding in vertebral fracture and kyphosis secondary to osteoporosis was the decrease in inspiratory muscle strength. Our results has demonstrated the importance of inspiratory muscle strengthening exercises in patients with osteoporosis.